Strategic Protocol in Crisis: A Conceptual Framework for Government Public Relations in State-Owned Energy Enterprises - Susetyo, Asti Sih; Pradana, Galang Yoga; Wahyuni, Kholifah; Subrata, Pramudya Ibnu (CITACONOMIA : Economic and Business Studies, 2026)
This conceptual article explores the operational paradox of PT Pertamina (Persero) as a National Oil Company (NOC) caught between its commercial mandates and the rigid bureaucratic protocols of the state. While protocol is traditionally viewed as a static administrative function, this study identifies it as a significant structural barrier—termed "bureaucratic inertia"—that impedes crisis communication agility, as evidenced by the 2025 Pertamax fuel crisis. Using a qualitative descriptive method and an integrative literature review, the research deconstructs the friction between Law No. 9 of 2010 on Protocol and the urgent demand for transparency in the digital era. The findings lead to the proposal of the "Agile Protocol" framework, which reconciles institutional dignity with communicative speed. This model is built upon two strategic pillars: Dynamic Formality, which simplifies hierarchical approval chains, and Digital Command Integration, which synchronizes protocol gestures with real-time social media monitoring. The study concludes that by shifting the paradigm from "honors for individuals" to "honors for the public interest," State-Owned Enterprises can preserve state authority while maintaining corporate reputation. Theoretically, this research extends Situational Crisis Communication Theory (SCCT) by integrating institutional honor as a critical variable in public sector reputation management.